The Effect of the Modified Free Inquiry Learning Model on Students’ Science Process Skills in Static Fluids - Hakim, Marsa Raihanida; Alatas, Fathiah (Universitas Islam Negeri Ar-Raniry, 2026)
This study aims to determine the effect of implementing the Modified Free Inquiry learning model on senior high school students’ science process skills in the topic of static fluids at SMA Negeri 1 Telukjambe, Karawang Regency, in the 2025/2026 academic year. The study employed a quasi-experimental research method using a nonequivalent control group design, with class XI 2 as the experimental group and class XI 5 as the control group. The research data were collected using a test instrument in the form of eighteen multiple-choice questions. The N-gain analysis results indicate a higher improvement in science process skills in the experimental group, with an N-gain value of 0.64, compared to the control group, which obtained an N-gain value of 0.25. Based on these findings, it can be concluded that the implementation of the Modified Free Inquiry learning model is effective in improving students’ science process skills in the topic of static fluids.